2018
DOI: 10.5935/1984-0063.20180031
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Anxiety disorder but not depression is associated with insomnia: a population based study

Abstract: Background: Insomnia is a common problem, however, its prevalence has never been examined in Indian population. Moreover, a number of psychiatric disorders have been found to be associated with insomnia in clinical population, but this association has scarcely been examined in general population.Methods: This epidemiological study was done in an urban and a rural population. Subjects were selected using Kish method. After obtaining informed consent, psychiatric disorders were diagnosed using Hindi version of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…[ 19 ] However, proportion to clinical insomnia was lower during the present study compared to the Greek population and remained at the level of pre-COVID-19 period. [ 20 ] Voitsidis et al . [ 19 ] showed that insomnia in the Greek population was a function of loneliness, uncertainty, depression, and COVID-19-related worries with a major contribution from two factors-depression and uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] However, proportion to clinical insomnia was lower during the present study compared to the Greek population and remained at the level of pre-COVID-19 period. [ 20 ] Voitsidis et al . [ 19 ] showed that insomnia in the Greek population was a function of loneliness, uncertainty, depression, and COVID-19-related worries with a major contribution from two factors-depression and uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a meta-analysis found that insomnia is a major risk factor of depression (OR = 2.83, 95%CI = 1.55–5.17) and anxiety (OR = 3.23, 95%CI = 1.52–6.85) 56 . On the other hand, depression and anxiety can also contribute to the development of insomnia 57 , 58 . Comorbid insomnia and psychiatric disorders may share common pathophysiology, such as similar alterations of arousal states 59 and levels of inflammatory markers 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study in youth found that anxiety preceded insomnia 73% of the time after adjustments for gender, race, and ethnicity (Johnson et al, 2006). Similarly, an epidemiological study in India revealed that anxiety was independently associated with insomnia after adjustments for other variables (Khan et al, 2018). Regarding ADHD, a study in the Netherlands showed that 43% of patients with ADHD reported significant insomnia (odds ratio = 2.66) and 41% reported short sleep duration (Wynchank et al, 2018).…”
Section: Introductionmentioning
confidence: 96%